Trauma-Informed Self-Efficacy and Practice Behaviors of Neonatal Intensive Care Unit Providers Caring for Mother–Infant Dyads Exposed to Opioids. - Cain, Shannon M; Held, Mary Lehman (Social Work Research, 2026)
Trauma-informed care (TIC) in medical settings, such as neonatal intensive care units (NICUs), is recommended but not widespread. This article examines trauma-informed (TI) perspectives and beliefs, previous training, self-efficacy, and practice behaviors of nurses and social workers who serve infants exposed in utero to opioids/opiates in Level III and IV NICUs in the United States. An online anonymous survey was conducted with NICU nurses and social workers (N = 69). Relationships between perspectives, beliefs and previous training, and self-efficacy and practice behaviors were examined using multiple regression. Results suggest that trauma awareness positively influences whereas judgment of maternal substance abuse negatively influences providers' level of TI practice behaviors; training in TIC and years of practice experience both positively influence providers' TIC self-efficacy. Implications exist for social work education and nursing education as well as practicing nurses and social workers in the NICU setting. Specifically, trainings in TIC and trainings that increase trauma awareness and decrease judgmental attitudes are needed. Additionally, increasing support for current NICU unit staff is recommended.